Auditing management systems for safety controls, alarms, and interlocks: How effective are your instrumented protective systems?. Issue 3 (6th February 2017) - Hochleitner, Monica; Roche, Eloise
Abstract : Functional safety audits evaluate the performance of the management systems and procedures required to keep safety controls, alarms, and interlocks (SCAI) working effectively. Organizations invest thousands, sometimes millions, of dollars installing automation systems in safety applications to minimize the risk of their enterprise. Return on investment in SCAI systems, and the achieved degree of risk reduction, can be negatively impacted by human error, such as inadequate installation, testing, maintenance, or operation of the automation systems. Administrative controls and organizational discipline are needed to identify and correct these errors. This article will provide an introduction to the purpose, key content, and planning of a functional safety audit. The case studies presented will illustrate how safety system effectiveness could have been improved if a detailed audit of the implemented SCAI had been conducted and the findings addressed in a timely fashion. © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 301–306, 2017